(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article presents an innovative approach to achieving efficiency in the general secondary education system, which serves as the initial stage of the broader educational structure. It focuses on the implementation of the cluster method derived from artificial intelligence technologies into the education sector, which plays a vital role in shaping the future of any country. Particular attention is paid to the use of cluster management in creating a favorable innovative environment among the teaching staff of general education schools, supporting higher education institutions in enhancing the scientific and methodological training of pedagogical personnel, and effectively organizing methodological work.